2011
DOI: 10.1016/j.febslet.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

RuvBl2 cooperates with Ets2 to transcriptionally regulate hTERT in colon cancer

Abstract: Edited by Varda RotterKeywords: RuvBl2 hTERT c-Myc Colon cancer a b s t r a c t Human cancers utilise telomerase to maintain telomeres and prohibit cell senescence. Human telomerase reverse transcriptase (hTERT), an essential component of this complex, is regulated at the level of gene transcription. Using SILAC-proteomic analysis and molecular studies, we identified the AAA+ ATPase, RuvBl2 as a transcriptional regulator of hTERT and established that this regulation is through cooperation with Ets-2. In colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Also RUVBL2 promotes tumorigenicity, is required for cell viability in hepatocellular, renal and breast cancers (Osaki et al., 2013) and is inversely associated with tumor differentiation grade and considered a marker of poor prognosis (Rousseau et al., 2007). In our cell models, RUVBL2 was highly expressed in more aggressive cells and advanced CRCs, in sharp and inverse relationship with PPARγ in line also with in vivo data (Flavin et al., 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Also RUVBL2 promotes tumorigenicity, is required for cell viability in hepatocellular, renal and breast cancers (Osaki et al., 2013) and is inversely associated with tumor differentiation grade and considered a marker of poor prognosis (Rousseau et al., 2007). In our cell models, RUVBL2 was highly expressed in more aggressive cells and advanced CRCs, in sharp and inverse relationship with PPARγ in line also with in vivo data (Flavin et al., 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, TNF significantly upregulated the expression of Ascl2, a Wnt target gene and key ISC transcription factor(19) in a dose-dependent manner (Fig 3A). TNF also upregulated the Ascl2 target gene Ets2(20) and Wnt-target CD44, both of which are implicated in stem cell maintenance and suppression of differentiation. TNF treatment did not alter the mRNA expression of differentiation markers (AP, Muc2, TFF3, Lys, CK20) or markers of proliferation (Ki67 and PCNA).…”
Section: Resultsmentioning
confidence: 99%
“…The expressions of these proteins are thought to be increased in many types of cancer (19). Flavin et al (12) showed positive reptin expression in 60% of colon cancer samples in their study. In this study, mean reptin mRNA expressions were also significantly higher in tumour tissues than in normal tissues in both total and breast cancer patients.…”
Section: Discussionmentioning
confidence: 79%
“…Most malignant cancers (85-90%) are known to show high telomerase activity for cellular immortality (12). Although the absence of telomerase in normal cells is considered a natural defence against the development of cancer, telomerase is thought to reappear in cancer cells through multiple mechanisms (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation